Associations between air pollution emitted from cookstoves and central hemodynamics, arterial stiffness, and blood lipids in laboratory and field settings - Walker, Ethan Sheppard, author; Peel, Jennifer, advisor; Clark, Maggie, advisor; Dinenno, Frank, committee member; Volckens, John, committee member; Wilson, Ander, committee member (Colorado State University. Libraries, 2019)
To view the abstract, please see the full text of the document.